Matrix Metalloproteinase Expression Patterns in Luminal A Type Breast Carcinomas. Issue 3 (6th June 2013) - Decock, J.; Hendrickx, W.; Drijkoningen, M.; Wildiers, H.; Neven, P.; Smeets, A.; Paridaens, R.
Abstract : Objective: Aberrant expression of individual matrix metalloproteinases has been associated with poor prognosis in various human carcinomas. The current study aimed at defining an RNA expression profile of various MMPs in breast cancer and correlating their expression with clinicopathological parameters. Methods: The RNA expression patterns of 6 MMPs (MMP2, MMP8, MMP9, MMP10, MMP11, MMP13) were determined in 25 breast carcinomas using quantitative RT-PCR and correlated with clinicopathological parameters, including menopausal status, tumor size and grade, and lymph node involvement. Results: We observed high MMP2 levels more frequently in premenopausal than in postmenopausal women ( p = 0.02). Analysis of luminal A type invasive ductal carcinomas (19/25), revealed an even stronger association of MMP2 with menopausal status ( p = 0.005). Within this subgroup, we also found a correlation between MMP11 and menopausal status ( p = 0.02). No correlation was found between MMP expressions and other clinicopathological parameters. In co-expression analyses MMP2-MMP10 and MMP8-MMP9 showed a weak correlation of their expression. Conclusions: Although this is a pilot study, our findings indicate that luminal A invasive ductal carcinomas commonly express high MMP2 and MMP11 levels in premenopausal breast cancer patients and suggest a co-regulation of MMP2-MMP10 and MMP8-MMP9.